Register Bahasa - Istiqo Mahanani (Program Studi Sastra Indonesia Universitas Jenderal Soedirman, 2025)
The result of this research is a description of the register which focuses on examining the form, meaning and function of the register. In the form section, the register data is divided into six parts based on the lingual units and the language of origin of the register. The function section is divided into four parts in the form of registers containing directive, referential/denotative/informative, metalingual and imaginative functions.